UJI ANTAGONISME CENDAWAN Trichoderma sp TERHADAP Ganoderma Boninense (PATOGEN PADA TANAMAN KELAPA SAWIT) SECARA IN VITRO - Putra, Sona Syah; Susanti, Yuliana; Alfiah, Lufita Nur (SINTA Journal (Science, Technology, and Agricultural), 2024)
Stem Root Rot (BPB) is a disease caused by the fungus Ganoderma Boninense. BPB results in low production of oil palm plants. Biological control using the fungus Trichoderma sp is an alternative that is currently being widely researched to control plant diseases. This research aims to determine the potential inhibitory ability of Trichoderma sp on the growth of G. Boninense in vitro. The research method used was double culture with isolates of Trichoderma Asperellum (T1), Trichoderma Asperellum (T2), Trichoderma Harzianum (T3) against G. Boninense. The research results showed that Trichoderma Asperellum (T1) had an inhibitory power of 72.3%, Trichoderma Harzianum (T3) had an inhibitory power of 72.2% and Trichoderma Asperellum (T2) had the highest antagonistic power reaching 92.5%. the three isolates of antagonistic fungi can inhibit the fungus G. Boninense